Structure and factorial invariance of a brief version of the Eating Attitudes Test in Peruvian university students - Ramos-Vera, Cristian; Basauri-Delgado, Miguel; Obregón, Stefanny Huamán; Saintila, Jacksaint (Frontiers in Psychology, 2023)
Background: University students often experience significant changes in their eating habits, which can increase the risk of developing eating disorders (ED). This situation calls for the creation of brief assessment tools to identify college students who may be most at risk. The aim of the study was to determine the psychometric properties of the Eating Attitudes Test-8 (EAT-8) in a Peruvian university population; additionally, the possible differences in the scores of the instrument according to sociodemographic variables, such as gender and age, were examined. Methods: A psychometric study was conducted on 610 participants (M = 24.3, SD = 2.16, and 61.5% female), aged 19 to 31 years, belonging to four universities of different professional careers. Results: The unidimensional eight-item model was found to have fit indices that confirm acceptable factorial validity (X2/df = 3.23, CFI = .984, TLI = .977, RMSEA = .061, SRMR = .049) and an internal consistency of .833 for the Cronbach's alpha coefficient and .838 for the McDonald's omega coefficient. In addition, the EAT-8 was reported to be invariant according to gender and age; likewise, there were no significant differences in the age and gender categories. Conclusion: The EAT-8 has solid psychometric properties, including validity, reliability, and invariance, in the Peruvian university population, which supports its ability to assess the risk of developing ED in this specific group.